Who you gonna call? Theorising everyday security practices in urban spaces with multiple security actors – The case of Beirut's Southern Suburbs. (October 2022) - Gunning, Jeroen; Smaira, Dima
Abstract: Who do urban residents turn to in everyday security incidents? Why do some go to the police in certain locations, others to armed nonstate actors or kinship networks? We explore the ways in which residents and security actors – state and nonstate – negotiate everyday (in)security in contested urban spaces with multiple security actors. We consider how hybrid security assemblages are shaped by physical and social space and how everyday security practices shape space. We use Beirut's Southern Suburbs (Dahiyeh) as a site of theorisation, bringing local vernacular experiences into dialogue with Bourdieu's concepts of capital, habitus, doxa and field to develop a spatially dynamic analytical framework. Using this framework, we map security actors' different types and sizes of capital and how this capital is affected by residents' habitus and doxa within the everyday security field. We introduce the notion of 'translocal habitus' to capture the impact of families' origins outside Dahiyeh on everyday security dynamics. The framework we develop contributes to the spatialisation, vernacularisation and pluralisation of everyday security studies, furthers the spatialisation of Bourdieu and adds to the literature on hybrid forms of governance. Our analysis is based on extensive fieldwork, including over 150 interviews and 'street chats' with residents and security actors in and around Dahiyeh.